Tobacco Dust Exposure Among Tobacco Workers in Jember Reduces Lung Function Capacity - Nofica, Cheila; Firdaus, Jauhar; Rachmania, Sheilla; Caesarina, Ancah (International Journal of Health and Information System, 2025)
This study investigated the association between urinary cotinine levels and lung function among tobacco workers in Jember Regency, a major tobacco-producing region in Indonesia. A total of 48 respondents were included based on specific inclusion and exclusion criteria. Urinary cotinine levels were measured using enzyme-linked immunosorbent assay (ELISA), and lung function was assessed via spirometry. Based on FEV1/FVC ratios, 58% of participants exhibited restrictive lung patterns, 29% showed obstructive patterns, and 13% had normal pulmonary function. Statistical analysis conducted using SPSS, with a significance level set at p < 0.05, indicated no statistically significant correlation between urinary cotinine levels and lung function.